EMPOWERMENT OF MARGINALIZED WOMEN THROUGH TRADITIONAL CLOTH WEAVING TRAINING AND ENTREPRENEURIAL EDUCATION - Kapa, Jimmy Ryan Samuel; Setijaningrum, Erna (Airlangga Development Journal, 2025)
The objective of this research is to observe and analyze the empowerment process carried out by the National Art Craft Office of East Nusa Tenggara for marginalized women through traditional cloth weaving training and entrepreneurial education. This study derives from a concern that the number of impoverished people in the area has risen significantly due to the impact brought on by COVID-19. The significance of poverty is of  great concern due to the fact that marginalized people, especially women, are the ones significantly impacted by this rise in poverty. This study employs a qualitative research approach and utilizes the exploratory case study method. Primary data is gathered through observations and interviews, while secondary data is collected through a study of available documentation. The results indicate that 5 out f 7 processes of community empowerment are conducted well and lead to the formation of five entrepreneurial groups with broad market reach.